ANCANG BANGUN ALAT INFORMASI TERDISPLAY VIDEOTRON BERBASIS MIKROKONTROLER - Muhdi .; Rudi Hariyanto; Anang Aris Widodo (SPIRIT, 2021)
Abstract : At present the media for delivering information in public places is growing. one of them by utilizingVideotron display for information delivery media, in general the information is displayed on paper and billboards.This method has the disadvantage that the information displayed is less attractive than it cannot be updated at anytime and it costs more if the information is displayed repeatedly. In this research, an information update tool hasbeen designed on an electronic information board using a microcontroller-based videotron display. This systemis useful for changing information that can be updated at any time. This system utilizes a microcontroller whichcan be programmed with powerled tools, various kinds of information that can be displayed including: Text, clock,image and audio video. In the design of information devices displaying videotron-based microcontractors showsthe results of testing the tool works well and testing tools with respondents who get good results too..Keywords: Information Board, Microcontroller Based Videotron